New Trends in Alloy Development, Characterization and Application - Ahmad, Zaki (IntechOpen, 2015)
The book explores the new developments that have taken place in recent years in the processing and application of aluminium alloys. The chapter on self diffusion shows a complete detail of the mechanism of diffusion in aluminium alloys and how it affects the strength. The chapter on native oxide films gives useful information on the films developed on commercial magnesium alloys. On the analytical side, the details of Mossbauer spectroscopy related to aluminium alloys fully described. One recent development in aluminium alloys is the controlling of pitting corrosion by the application of superhydrophobic coatings. Complete details of the theory and application of hydrophobicity related to aluminium alloys is shown in the two chapters related to hydrophobicity. It is hoped that this book will be found useful by researchers and general readers in the areas described in the book.